2019
DOI: 10.1007/s13205-019-1583-1
|View full text |Cite
|
Sign up to set email alerts
|

Low-cost shoot multiplication and improved growth in different cultivars of Canna indica

Abstract: Canna (Canna indica L.) is an ornamental landscape plant used specially for the garden borders and beds. It grows in tropical and subtropical countries including India. Canna is a less explored crop, mainly because it is a slow growing monocot with extremely hard seed coat and difficult to establish in vitro, as bacterial contamination is carried through the soil-grown rhizome. Many cultivars (ca. 150) of canna are being maintained in the garden germplasm of National Botanical Research Institute. To obtain 100… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…India canna is one of the most popular flowering ornamental plants for garden borders and grows in tropical and subtropical countries, including India. [ 69 ] It is another plant showing a good superhydrophobic property of 165° ± 2°. In addition to these two plants, there are many other creatures with hierarchical micro‐ and nanostructures, such as the famous self‐cleaning plants like lotus leaf, rice leaf, and so on.…”
Section: Two Different Scales In Superhydrophobic Structuresmentioning
confidence: 99%
“…India canna is one of the most popular flowering ornamental plants for garden borders and grows in tropical and subtropical countries, including India. [ 69 ] It is another plant showing a good superhydrophobic property of 165° ± 2°. In addition to these two plants, there are many other creatures with hierarchical micro‐ and nanostructures, such as the famous self‐cleaning plants like lotus leaf, rice leaf, and so on.…”
Section: Two Different Scales In Superhydrophobic Structuresmentioning
confidence: 99%
“…When compared to Cyperus alternifolius and Phragmites australis, Canna indica outperforms them in terms of pollution reduction and greenhouse gas emissions [18,27]. Canna indica have a fibrous roots structure that produces high aerobic conditions throughout the CW, allowing for more removal [26].…”
Section: Plants Used In Cwmentioning
confidence: 99%
“…Canna indica L. (Figure 1) is one of the most common flowering ornamental plants for garden borders and beds, and occasionally grown as potted plants [27]. Recent investigations have revealed that the plant has medicinal value in addition to its ornamental value [29].…”
Section: About Canna Indica Lmentioning
confidence: 99%
“…However, the regeneration system produced by the traditional organotype method also had some defects. For example, the plants were seriously polluted in the process of culture, the browning rate was high, and the reproduction coe cient and the differentiation rate were low (Purshottam et al 2019;Mitrofanova et al 2017). Previous studies have reported that the leaves of C. indica L. were used to induce callus and regenerated plants by somatic embryogenesis.…”
Section: Introductionmentioning
confidence: 99%